A Recent Whole-Genome Duplication Divides Populations of a Globally Distributed Microsporidian - Williams, Tom A. (Oxford University Press, 2016)
The Microsporidia are a major group of intracellular fungi and important parasites of animals including insects, fish, and immunocompromised humans. Microsporidian genomes have undergone extreme reductive evolution but there are major differences in genome size and structure within the group: some are prokaryote-like in size and organisation (<3 Mb of gene-dense sequence) while others have more typically eukaryotic genome architectures. To gain fine-scale, population-level insight into the evolutionary dynamics of these tiny eukaryotic genomes, we performed the broadest microsporidian population genomic study to date, sequencing geographically isolated strains of Spraguea, a marine microsporidian infecting goosefish worldwide. Our analysis revealed that population structure across the Atlantic Ocean is associated with a conserved difference in ploidy, with American and Canadian isolates sharing an ancestral whole genome duplication that was followed by widespread pseudogenisation and sorting-out of paralogue pairs. While past analyses have suggested de novo gene formation of microsporidian-specific genes, we found evidence for the origin of new genes from noncoding sequence since the divergence of these populations. Some of these genes experience selective constraint, suggesting the evolution of new functions and local host adaptation. Combining our data with published microsporidian genomes, we show that nucleotide composition across the phylum is shaped by a mutational bias favoring A and T nucleotides, which is opposed by an evolutionary force favoring an increase in genomic GC content. This study reveals ongoing dramatic reorganization of genome structure and the evolution of new gene functions in modern microsporidians despite extensive genomic streamlining in their common ancestor.